#TITLE_ALTERNATIVE# - MESAYU ANDARI (NIM : 12211068), ARIZKA
This paper present the result of feasibility study aimed at extending the production life of an oil field in Indonesia through EOR (Enhanced Oil Recovery) employing the huff and puff CO2 injection technique. This research used a modeling approach to optimize sweep efficiency by Immiscible CO2 Injection and apply smart completion on perforations at the well. A compositional simulation model using detailed geologic characterization was built to optimize Immiscible CO2 injection design. The model is radial model with production and injection well (well M-14) are on the center of the model of Meruap Field. The Peng-Robinson equation of state (EOS) was chosen to describe the phase behavior during the injection phase. Several sensitivity runs were made to improve the CO2 sweep efficiency and increase the oil recovery. This study found that CO2 injection is influenced by rate of injection, volume of CO2, and soaking time. Greater volume of CO2and longer soaking time will lead to more increment of reservoir pressure. Meanwhile, the slow rate of injection was found to be efficient in the immiscible CO2 injection. Immiscible CO2 injection mechanism that have been analyzed from this simulation are; viscosity reduction, oil swells, and extraction of the light components of oil. Application smart completion design in immiscible CO2 injection was found declining reservoir pressure gradually during production period, wherein the immiscible conventional CO2 injection pressure drops faster and steeper. However, the application of smart completion design at a high injection rate and high CO2 slug volume will not be optimal because of the increment of reservoir pressure is not similar to conventional procedure after injection period. It is inversely proportional on slow rate (7 ton per day) and 1000 ton CO2 slug volume simulation, the application of smart completion design by Injection-Spacer-Producer configuration were found more increment on cumulative oil recovery due to proper placement of production perforation.